Aplicação de gestão de treinos em academias com suporte de Inteligência Artificial(IA) - Pelizzoni, Natan Osvald (2024)
This project presents a web application designed to support the management of gym training routines, incorporating integration with Artificial intelligence (AI). The system utilizes user data, such as age, weight, height, fitness goals, weekly frequency, health restrictions, and more, to generate personalized workout plans through the GPT-3.5 Turbo AI model from OpenAI. By automating the workout planning process, the application aims to optimize the time of fitness professionals, allowing them to focus on providing better guidance and support to gym members during their exercises. The project details the selection of technologies, their application, the design and implementation process, as well as the results obtained from validating the application in a real gym environment. It concludes that integrating AI into a management platform can be a valuable ally in optimizing professionals’ time while maintaining expert oversight of the AI-generated suggestions.